PROFIL KEMAMPUAN MOTORIK KASAR SISWA SD INPRES PERUMNAS TINGGEDE BERDASARKAN TES TGMD-2 (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aims to describe the gross motor skills of students at SD Inpres Tinggede Perumnas using the Test Of Gross Motor Development Second Edition (TGMD-2). The research employed a descriptive quantitative approach involving 10 students aged nine to ten years. The assessment covered two major components, locomotor skill and object control skills, with each performance evaluated through specific criteria and two trials per skill.the result show that the average locomotor score was 39.7, categorized as good, although several students were still ini the fair category, indicating thay some locomotor patterns had not developed optimally. The object control component showed a higher average score 41.6, with most students categorized as good to very good.  These findings suggest that students have more frequent exposure to activities involving object manipulation compared to locomotor-based activities.  Overall, the gross motor skills of the students are at an adequate level for their age group. The results provide useful information for physical education teachers to design targeted learning strategies that support students motor development